Re‐evaluation of konjac gum (E 425 i) and konjac glucomannan (E 425 ii) as food additives - Mortensen, Alicja (EFSA J, 2017)
The present opinion deals with the re‐evaluation of konjac (E 425), comprising konjac gum (E 425 i) and konjac glucomannan (E 425 ii) when used as food additives. Following the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel considered that current use of konjac (E 425) was limited in all food categories to maximum permitted level (MPL) of 10 g/kg, and that the calculated indicative refined exposure assessment for all population groups was below 0.1 mg/kg body weight (bw) per day for the general population (mean and high level). Konjac gum and konjac glucomannan were unlikely to be absorbed intact and were significantly fermented by intestinal microbiota. The available database on toxicological studies was considered limited, however, no relevant adverse effects were seen in rats and dogs in 90‐day feeding studies according to the SCF, the no‐observed‐effect level (NOEL) in rats being 1,250 mg konjac glucomannan/kg bw per day. Konjac gum and konjac glucomannan were of no concern with respect to the genotoxicity. After a daily dosage of 3,000 mg in adults for 12 weeks, several individuals experienced abdominal discomfort including diarrhoea or constipation. The Panel concluded that there was no need for a numerical acceptable daily intake (ADI) and that there was no safety concern for the general population at the refined exposure assessment for the reported uses of konjac gum (E 425 i) and konjac glucomannan (E 425 ii) as food additives under the current conditions of use of 10 g/kg. The Panel agreed with the conclusions of the SCF (1997) that the uses of konjac (E 425) as an additive at the levels up to 10 g/kg in food are acceptable, provided that the total intake from all sources stays below 3 g/day.